Abraham, høflighedens ridder - Jensen, Hans Jørgen Lundager (Dansk Teologisk Tidsskrift, 2011)
In the Hebrew Bible, the do-ut-des-relationship, so often used to describe the exchange between the divine and the human realms, designates the exchange between human partners. Professional exchange, by contrast, has a problematic status in the Hebrew Bible with its wellknown negative views on trade, traders, and their wealth. Yet in this article, “Abraham, knight of courtesy”, I argue that Abraham in Genesis is presented as a person of great wealth with frequent contacts across social and ethnical borders and with great skills for negotiations. His commitment to family and family religion does not rule out frequent contacts with persons from other cultures and religions. Some of the Abraham narratives may therefore have been written also as a tacit critique of more dominating, and more exclusive, theological currents in the Hebrew Bible.